MEDIA PEMBELAJARAN PEMBANGKIT LISTRIK TENAGA SURYA DALAM PENGUKURAN ARUS DAN TEGANGAN LISTRIK PADA RANGKAIAN SERI PARALEL - Suryadi, Putu Dita Suryadi; Arsa, I Putu Suka; Prasetya., Wayan Mahardika (Universitas Pendidikan Ganesha, 2023)
This research aims to create and develop learning media for solar power plants in electrical engineering education study programs at Ganesha University of Education that can be used to support the learning process so that it makes it easier for employers to deliver material related to solar power plants. This learning medium combines the main components of a solar power plant so that it gives students the opportunity to assemble a solar power plant in a simple way. The method used in this research is research and development (research and Development). The results of panel voltage measurements based on the intensity of sunlight in series average 20 Vdc in the morning, 38.1 Vdc in the afternoon, and 37.4 Vdc in the afternoon, while in parallel circuits the average is 18.4 Vdc in the morning, 20.6 Vdc in the afternoon, and 20 Vdc in the afternoon. The study used a questionnaire as a reference for data collection, which was filled out directly by content experts, media experts, and Electrical Engineering Education students as respondents. The results of the content expert validation test obtained a proportion of 95.83% with very decent qualifications; the validation test from media experts obtained a proportion of 97.82% with very decent qualifications; the results of the small group validation test with 5 students as respondents obtained the lowest average score of 45 and a proportion of 100% in the very high category; and the results of the large group validation test with 10 students as respondents obtained the lowest average score of 45 and a proportion of 100% in the very high category. Based on the results of validation tests from experts and students, trainers for solar power generators are suitable for use in supporting the learning process in the Electrical Engineering Education Study Program.